Modeling the mobile communication service based on PI-calculus - KANG Hui1; ZENG Ying-ying1; LIU Zhi-yong1 (Tongxin xuebao)
In order to solve the problem of not interworking the increment service provided by difference services providers in current mobile communication service,mobile communication process were defined as multiple independent Web services.The connection initialization,base station switching and mobile communication process were modeled by using PI-calculus.The PI-calculus expressions were encapsulated and combined.Modeling for PI-calculus can optimize the mobile communication service,and discover problems as soon as possible in the design stage to eliminate repeating business between difference service providers and to ensure their reusability and interoperability.